Quality of Work Life and Job Performance Among Malaysian Executives in The Electrical and Electronics Industry in Selangor - Beh, Loo See (2005)
This study was to determine the relationships of selected variables, namely career satisfaction, career achievement, career balance, organizational climate and organizational constraint in predicting the quality of work life (QWL) and their relationships to job performance. The survey research provided a method of empirical verification utilizing stratified random sampling to determine the relationships between variables at the time of study. The sample consisted of 475 executives from the electrical and electronics industry. The selection of respondents involves a complete list of electrical and electronics companies registered with Malaysian Industrial Development Authority (MIDA). The quantitative data were subjected to various descriptive-correlation statistical analyses, multiple regression, mediation anaIyses, and structural equation modeling. In this study, the findings support the relationship between the independent variables and QWL. All the variables explained 79.1% of QWL, thus presenting a good model of the significant exogenous variables and fairly accurate. QWL is a significant predictor in determining Job Performance. However, the effect of the QWL as a mediator between the exogenous variables and Job Performance is not found. The results show that the executives are satisfied with their level of quality of work life, career achievement, career satisfaction, and organizational climate but not in terms of career balance and the organizational constraints they faced in the organization. Future research suggestions were advocated, in particular, the replication of this study to other population. Further work is also needed to develop and identify avenues and constructs for quality of work life and career related development within the organization as a relatively young field